2017
DOI: 10.1039/c7nr05731h
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dots: promising biomaterials for bone-specific imaging and drug delivery

Abstract: Bone-related diseases and dysfunctions are heavy burdens on our increasingly aged society. One important strategy to relieve this problem is through early detection and treatment of bone-related diseases. Towards this goal, there has been constant interest in developing novel bone-specific materials for imaging and drug delivery. Currently, however, materials that have high affinity and specificity towards bone are very limited. Carbon dots (C-dots) synthesized from carbon nanopowder bind to calcified bones in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 46 publications
1
88
0
Order By: Relevance
“…Moreover, Leblanc's group has recently demonstrated that fabrication of C‐dots with intrinsic bone‐binding properties does not necessarily require special precursors . This particular class of C‐dots, with diameters ranging from 4 to 6 nm, was synthesized via simple acid oxidization of carbon nanopowder .…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Leblanc's group has recently demonstrated that fabrication of C‐dots with intrinsic bone‐binding properties does not necessarily require special precursors . This particular class of C‐dots, with diameters ranging from 4 to 6 nm, was synthesized via simple acid oxidization of carbon nanopowder .…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…Further, even functionalized with a bone‐seeking group (glutamic acid), CD3 still failed to bind to bones in vivo (GA‐CD3, Figure E3). Encouragingly, the functionalization of the C‐dots did not alter their binding ability towards bone (Figure F1‐F3), which demonstrated their great potential in bone‐specific bioimaging and drug delivery . The highly specific bone‐binding ability of this type of C‐dots might be due to the rich presence of carboxyl groups on their surfaces .…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 CNDs can be readily internalized by different types of cells: several research groups have evaluated their potential as bioimaging agents in cellular or in vivo environments. [28][29][30] Moreover, CNDs have emerged as a versatile platform for the design of novel drug delivery systems with promising studies reporting the use of CNDs as nanocarriers for the delivery of therapeutic agents, [31][32][33] such as doxorubicin. [34][35][36] CNDs retain their luminescence after the loading of the drugs, either through electrostatic interaction or covalent binding, serving not only as a vehicle for drug delivery, but also for cell imaging.…”
Section: Introductionmentioning
confidence: 99%
“…1 For their unique properties, such as high water solubility, tunable emission, low toxicity, and facile preparation, CDs have received much attention and show great application value in many elds including biological imaging, cancer treatment, sensors, photoelectric devices and catalysis. [2][3][4][5] For example, light-emitting diodes using CDs to work as colour conversion layers have been reported by several groups and show a broad development prospect. [6][7][8] Though various precursors and methods have been applied on the preparation of CDs, most of the products show bluelight-region emission.…”
Section: Introductionmentioning
confidence: 99%